Validation of Single Well Geothermal Heat Pump System by Scaled Model Experiments (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
For shallow geothermal applications, the U-tube ground source heat pump (GSHP) system, the standing column well(SCW) geothermal heat pump system, and the forced external circulation single well(FECSW) geothermal heat pump system are recognized as the most advanced methods of geothermal cooling and heating systems, either by using no groundwater or by recycling groundwater. In order to improve the heat extraction efficiency of these single-well modes, it is vital to experimentally analyze the heat extraction efficiency in different experimental environments that can be encountered under realistic conditions. Based on the 1:20scaled model we design 10 experimental scenarios considering different experimental conditions, such as soil moisture, groundwater convection, heat conduction, abstraction and injection interval selection, and compared the heat extraction efficiency according to the scheme. The experimental results shows that the order of increasing heat extraction capacity is U-tube, SCW, FECSW. Also, in three methods, the heat extraction capability is changed by the water flow into the ground, ground moisture, operating approaches, etc. The results of the scaled model experiments are used as a comparative validation data for numerical simulation of a single well geothermal heat pump system and contribute to the development of modeling method of geothermal single well in real conditions.